HEalth professionals Responding to MEn for Safety (HERMES): Mixed methods evaluation of a pilot sexual health intervention for gay, bisexual and other men who have sex with men experiencing domestic violence and abuse - Ana Maria Buller; Giulia Ferrari; Alexandra Bleile; Gene S. Feder; Petra J. Brzank; Loraine J. Bacchus (PLoS ONE, 2025)
Background Domestic violence and abuse (DVA) is a violation of human rights that damages the health and well-being of—gay, bisexual and other men who have sex with men (gbMSM). Sexual health services provide a unique opportunity to assess for DVA and provide support. This study explores the feasibility and acceptability of Healthcare Responding to Men for Safety (HERMES), a pilot intervention aimed to improve the identification and referral of gbMSM experiencing DVA in a London NHS Trust. Methods The before and after mixed method evaluation of the intervention included semi-structured interviews with 21 sexual health practitioners, 20 matched pre-post questionnaires, and an audit of 533 patient records to assess identification and referral of gbMSM experiencing DVA. Results HERMES increased practitioners’ self-reported preparedness and confidence in enquiring, identifying and responding to gbMSM experiencing DVA. HERMES increased staff awareness of DVA among these patients, which led to higher identification practices in their work. There was a significant increase in the identification and reporting practices of trained staff (0% to 30%), with 6 (5%) DVA cases identified. However, as far as we could determine, none of these patients contacted the support agency. Conclusions HERMES proved successful in raising staff awareness, provided tools that increased identification and a referral pathway to an external specialist DVA service for the LGBT community. However, the poor uptake of the referral service indicates a need for further exploration of the help-seeking behaviour of gbMSM experiencing DVA and whether they would prefer to receive support within a sexual health service. Reinforcement training and clinical supervision is needed to sustain positive changes in practice over time and address potential challenges posed by staff turnover. Initial training should be conducted through face-to-face sessions with a combination of in-person and e-learning materials and followed by in-person and online reinforcement activities.